The Effect of Strategic Operational Effectiveness Analysis of Crowdsourcing Initiatives - Gbenga Fapohunda; Asunmo Olakunle Olayide (Communications of International Proceedings, 2023)
Over the years, crowdsourcing has become an important strategy for organizations looking for answers to improve their innovative performance. The aim of the study is to examine the effect of crowdsourcing and crowd voting on organizational performance. The result of the study shows that crowdsourcing and crowd voting have a significant effect on organizational performance. The study concluded that crowd creation and crowd voting are major factors that influence the performance of organization. The study recommended that managers should implement crowd creation policies in their organization, so as to increase their performance. Also, the management of companies should pay more attention to crowd voting as this will boost their performance.
Keywords: Crowdsourcing; Crowd Voting; Crowd creation; Organization; Performance